A community outbreak of Legionnaires’ disease caused by outdoor hot tubs for private use in a hotel - Gumá, Mercedes; Drasar, Vladimir; Santandreu, Beatriz; Cano, Rosa; Afshar, Baharak; Nicolau, Antonio; Bennassar, Magdalena; Barrio, Jorge del; Crespi, Pau; Crespi, Sebastian (Frontiers in Microbiology, 2023)
During the period October - November 2017, an outbreak of Legionnaires’ disease involving 27 cases occurred in the tourist area of Palmanova (Mallorca, Spain). The majority of cases were reported by the European Centre of Disease Prevention and Control (ECDC) as travel associated cases of Legionnaires’ disease (TALD). Most cases belonged to different hotel cluster alerts. No cases were reported among the local population residing in the area. All tourist establishments associated with one or more TALD cases were inspected and sampled by public health inspectors. All relevant sources of aerosol emission detected were investigated and sampled. The absence of active cooling towers in the affected area was verified, by documents and on-site. Samples from hot tubs for private use located on the terraces of the penthouse rooms of a hotel in the area were included in the study. Extremely high concentrations (> 106 CFU/L) of L. pneumophila, including the outbreak strain, were found in the hot tubs of vacant rooms of this hotel thus identifying the probable source of infection. Meteorological situation may have contributed to the geographical distribution pattern of this outbreak. In conclusion, hot tubs for private use located outdoors should be considered when investigating community outbreaks of Legionnaires’ disease of unclear origin.